2001
DOI: 10.2304/forum.2001.43.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Testing, Testing, Testing ... Investigating Student Attitudes Towards, and Perceptions of, Eleven Years of Testing and Target Setting

Abstract: write in deep appreciation of Caroline Benn's loyalty and friendship, and her incalculable contribution to the comprehensive school movement. A letter that she wrote to Brian Simon only a few weeks before she died is also included, testament to her unswerving support, whatever her personal circumstances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…It can therefore offer potential for control and ownership through being sensitive to particular aspirations for teaching and learning (Blanchard 2003). Nevertheless, this potential may not always be fulfilled if teachers and students simply just go through the motions without necessarily understanding or engaging with the process (Worrall 2001). The role of the student in setting and owning targets is sometimes tenuous, with some evidence that students have trouble understanding what their targets are (Male 2000;Worrall 2001).…”
Section: Student Involvement and Ownershipmentioning
confidence: 99%
See 1 more Smart Citation
“…It can therefore offer potential for control and ownership through being sensitive to particular aspirations for teaching and learning (Blanchard 2003). Nevertheless, this potential may not always be fulfilled if teachers and students simply just go through the motions without necessarily understanding or engaging with the process (Worrall 2001). The role of the student in setting and owning targets is sometimes tenuous, with some evidence that students have trouble understanding what their targets are (Male 2000;Worrall 2001).…”
Section: Student Involvement and Ownershipmentioning
confidence: 99%
“…Nevertheless, this potential may not always be fulfilled if teachers and students simply just go through the motions without necessarily understanding or engaging with the process (Worrall 2001). The role of the student in setting and owning targets is sometimes tenuous, with some evidence that students have trouble understanding what their targets are (Male 2000;Worrall 2001). Day (1998) advocates target setting practice that includes behaviour and experience targets in addition to those regarding attainment.…”
Section: Student Involvement and Ownershipmentioning
confidence: 99%
“…There is also more and more evidence about the damaging effects of over testing on pupils themselves. Non Worrall, in an article for FORUM (Worrall, 2001) gave an account of a generation of young people who by the time they face their GCSE and AS level examinations feel they have been 'tested out'. Harlen & Deakin Crick (2002) have found that repeated testing, including practice tests, reinforces the low self-image of lower attaining pupils, which widens the gap between higher and lower attaining pupils.…”
Section: What Are the Consequences Of The Present Situation?mentioning
confidence: 99%